Contemporary State Language Policy of Ukraine: A European Dimension - Kuts, Yuri; Sergeyeva , Olena (Theory and Practice of Public Administration, 2019)
The article analyzes the situation concerning the problems of realization of constitutional requirements of development and use of languages ​​in Ukraine.The processes of russification have not yet been discontinued and are becoming more sophisticated; language rehabilitation of citizens of Ukraine is deliberately inhibited in some places; higher education has often been provided in the Russian language and the mechanisms of introducing the state language into the educational process are proceeding rather slowly; the numerous corps of civil servants, especially at the local level, are very reluctant and weak to transfer business communication into Ukrainian.It is proved that in the sphere of domestic policy there should be every support for the state language, which is one of the symbols of statehood. Its main function is to provide a single political, economic and educational space throughout the country. The language policy of the state should be implemented on the basis of clearly developed language legislation. The state language policy of Ukraine has a sufficient set of formalized and separate goals, as well as other properties and qualities, to distinguish it into a separate type of the state policy.Each of the languages ​​existing in Ukraine is subject to legal regulation in the state language policy of Ukraine, as they are the subject of business, cultural, scientific and other activities. The state language of Ukraine is also an instrument of public administration which serves to promote the will of the people and the will of the state.